2010
DOI: 10.1002/9783527631995.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of the CXCR3 Receptor

Abstract: A search for T lymphocyte-specific chemokine receptors led to the discovery of the CXCR3 receptor in 1996. A novel cDNA was isolated from a human CD4 þ T cell library and the encoded GPCR proved to have affinity for chemokines [1]. Further work revealed that CXCR3 consists of 368 amino acids which assemble in a typical seven-transmembrane a-helical architecture. Chapter 2 has described in detail the structural characteristics of the chemokine receptor family and CXCR3 fits this general picture. CXCR3 exhibits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…In view of the potential therapeutic interest in CXCR3 blockade in diseases like rheumatoid arthritis and allograft rejection (Wijtmans et al, 2011), many different drug discovery programs have yielded several distinct chemical classes of small-molecule compounds, including antagonists as well as a few agonists (Wijtmans et al, 2008(Wijtmans et al, , 2011, such as the 8-azaquinazolinone compounds from Amgen Inc. (AMG487, (R)-N- (1-(3-(4-ethoxyphenyl)-4-oxo-3,4-dihydropyrido[2,3-d]pyrimidin-2-yl)ethyl)-N-(pyridin-3-ylmethyl)-2-(4-trifluoromethoxy)phenyl)acetamide; Washington, D.C.) and Neurocrine Biosciences pyrimidin-2-yl)ethyl)-2-(4-fluoro-3-(trifluoromethyl)phenyl)-N-(pyridin-3-ylmethyl)acetamide; San Diego, CA), which bind to CXCR3 with affinities in the nanomolar range (Heise et al, 2005;Johnson et al, 2007;Verzijl et al, 2008). Moreover, a piperazinyl-piperidine compound class containing ligands with nanomolar CXCR3 affinities was reported by Schering Plough (now Merck Sharp & Dohme, Kenilworth, NJ) (Mcguinness et al, 2009;Kim et al, 2011;Shao et al, 2011;Nair et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In view of the potential therapeutic interest in CXCR3 blockade in diseases like rheumatoid arthritis and allograft rejection (Wijtmans et al, 2011), many different drug discovery programs have yielded several distinct chemical classes of small-molecule compounds, including antagonists as well as a few agonists (Wijtmans et al, 2008(Wijtmans et al, , 2011, such as the 8-azaquinazolinone compounds from Amgen Inc. (AMG487, (R)-N- (1-(3-(4-ethoxyphenyl)-4-oxo-3,4-dihydropyrido[2,3-d]pyrimidin-2-yl)ethyl)-N-(pyridin-3-ylmethyl)-2-(4-trifluoromethoxy)phenyl)acetamide; Washington, D.C.) and Neurocrine Biosciences pyrimidin-2-yl)ethyl)-2-(4-fluoro-3-(trifluoromethyl)phenyl)-N-(pyridin-3-ylmethyl)acetamide; San Diego, CA), which bind to CXCR3 with affinities in the nanomolar range (Heise et al, 2005;Johnson et al, 2007;Verzijl et al, 2008). Moreover, a piperazinyl-piperidine compound class containing ligands with nanomolar CXCR3 affinities was reported by Schering Plough (now Merck Sharp & Dohme, Kenilworth, NJ) (Mcguinness et al, 2009;Kim et al, 2011;Shao et al, 2011;Nair et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Overexpression of the CXCR3 receptor and/or its ligands (CXCL9, CXCL10, CXCL11) is often observed in rheumatoid arthritis and transplant rejection (Lacotte et al, 2009). In the past decade, many efforts have focused on the discovery of small molecule CXCR3 antagonists, leading to the disclosure of ligands with a multitude of different chemotypes (Wijtmans et al, 2008(Wijtmans et al, , 2010 …”
Section: Introductionmentioning
confidence: 99%
“…Besides the distribution in the CNS, H 3 R is present in the PNS as well, including the cardiovascular system, the airways and the gastrointestinal tract [13]. Over the years, several lines of evidence have suggested that H 3 R might be a therapeutic target in cognitive disorders, including attention deficit hyperactivity disorder (ADHD), Alzheimer's disease (AD) and schizophrenia, as well as in other therapeutic areas such as sleep disorders, pain, obesity and allergic rhinitis [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Vast amounts of literature on H 3 R receptor ligands have been published and they have been described in a number of recent reviews [4,14,15,[33][34][35]. A key theme in the development of these ligands was to provide the means to capitalize on therapeutic promise of H 3 R, both through tool compounds as well as through advanced drug candidates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation